Perubahan Kualitas Perairan Terhadap Keberlangsungan Usaha Budidaya Rumput Laut Di Pulau Pari - Arum Sitaresmi, Deyan; Zahra, Ashila Fitria; Rohmana; Adhitama, Rafif Bima; Rosadi, M Imron; Citra, Leysha Adinda; Lestari, Citra; Kusumawati, Lia (Jurnal Sains Geografi, 2024)
This research aims to analyze the water quality of Pari Island for seaweed cultivation. The main challenge involves the decline in seaweed production and quality, especially after the 2013 reclamation project. This research uses quantitative methods with primary and secondary data collection, water quality analysis involving parameters such as depth, temperature, salinity, pH and brightness, evaluated through the IDW method and weighting. The research results reflect an increase in temperature and salinity, resulting in a decrease in the quality of seaweed cultivation land on Pari Island. Reclamation factors and industrial activities also influence this condition. The seaweed cultivation land suitability map shows a significant decline from 2017 to 2023. The conclusion from research on changes in Pari Island's water quality regarding the sustainability of seaweed cultivation no longer supports optimal seaweed cultivation. The research recommendations highlight the need for sustainable planning and mitigating industrial impacts to support the growth of the seaweed cultivation industry on Pari Island.